Refocusing on COVID-19 Local Budgets and Achieving Absorbability of the Recovery of the Local Economic Situation and Public Health: A Systematic Study - Alfarizi, Muhammad (Ministry of Home Affairs, 2023)
After the stipulation of COVID-19 as a national pandemic, government policies have automatically been adjusted. This, of course, is no exception to the main problems related to financial settlements carried out by the central government and local governments. The State mandates regional governments to carry out various efforts, including budget refocusing in handling COVID-19. Synergy understanding of policy refocusing of the budget if we focus on studies carried out by regional expenditures in handling the COVID-19 pandemic, efforts need to be made for further evaluative surgery, especially about managing public health and regional economic recovery. This evaluation research was conducted by systematically reviewing the process of refocusing regional budgets and implementation and the impacts obtained from various supporting scientific literature plus supporting data from existing Regional Governments with PRISMA Analysis. This research can at least state the success of almost all local governments in carrying out the budget function in dealing with the COVID-19 pandemic in terms of public health and economic recovery. The central role of the Regional Government, especially the Regional Planning and Development Agency and the Financial Management Agency, is to encourage budget absorption through communication and regulatory functions. Part of the community is needed in Government Programs, especially in dealing with COVID-19. It is essential in this study that budget refocusing is only sometimes carried out because it is related to the country's fiscal stability.